2010
DOI: 10.1007/s12664-010-0014-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pegylated IFN alfa 2b alone or in combination with ribavirin in thalassemia major with chronic hepatitis C

Abstract: In patients with TM and chronic HCV infection, pegylated interferon alfa 2b and ribavirin combination therapy achieves a higher SVR rate than pegylated interferon alone, and is well tolerated except for an increase in blood transfusion requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The overall reported SVR rates in children are 35.6% with standard interferon, 42.8% with Peg-IFNa monotherapy, 46.8% with standard IFNa with RBV combination and 69% with Peg-IFNa and RBV combination. 83 Sood et al 84 reported SVR rates of 70% with Peg-IFNa2b and RBV in thalassemic children between 3 and 15 years of age with transfusion acquired chronic HCV infection.…”
Section: Management Of Hepatitis C Virus In Pediatric Age Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall reported SVR rates in children are 35.6% with standard interferon, 42.8% with Peg-IFNa monotherapy, 46.8% with standard IFNa with RBV combination and 69% with Peg-IFNa and RBV combination. 83 Sood et al 84 reported SVR rates of 70% with Peg-IFNa2b and RBV in thalassemic children between 3 and 15 years of age with transfusion acquired chronic HCV infection.…”
Section: Management Of Hepatitis C Virus In Pediatric Age Groupmentioning
confidence: 99%
“…The SVR rates with Peg-IFNa/RBV combination therapy are around 50% for genotype 1 and 80% for genotype 2/3 infections. 1,2 In the case of genotype 2/3, SVR rates of as high as 84-95% have been reported from some Southeast Asian countries. 3 Currently, there are several comprehensive and up-todate guidelines, issued by leading authorities such as AASLD and EASL, for the management of CH-C. [4][5][6][7] However, there are many special issues which merit attention prior to the implementation of any such guidelines for the management of CH-C in India.…”
mentioning
confidence: 99%
“…Anaemia is the most common side effect of PEG-IFN/RBV and patients with hemoglobinopathies require a higher number of blood transfusions when they are treated with PEG-IFN/RBV [21]. Indeed, in our short case series, all patients needed more blood transfusions to overcome reduction of hemoglobin.…”
Section: Discussionmentioning
confidence: 96%
“…However, adding RBV to IFN significantly improved treatment outcomes so that SVR rates increased up to 54-56% [22][23][24], and this approach has been accepted as the mainstay of CHC management. This combination has been well tolerated even in thalassemia major patients, except for an increase in blood transfusion requirements because of RBV side effects [25].Approximately 70-75% of patients who are infected with HCV in the USA are infected with genotype 1, which is associated with a lower rate of response. Currently, standard treatment with PEG-IFN and RBV results in less than 50% SVR rates in these patients.…”
mentioning
confidence: 99%
“…However, adding RBV to IFN significantly improved treatment outcomes so that SVR rates increased up to 54-56% [22][23][24], and this approach has been accepted as the mainstay of CHC management. This combination has been well tolerated even in thalassemia major patients, except for an increase in blood transfusion requirements because of RBV side effects [25].…”
mentioning
confidence: 99%